Viral vectors in neurodegenerative diseases: immune responses and therapeutic applications - Wang, Yifei; Mu, Siyu; Liu, Fangxi (Frontiers in Neurology, 2025)
Gene transfer-based therapies utilizing viral vectors have undergone remarkable advancements and hold significant promise in addressing neurodegenerative diseases in recent years, whose potential mechanisms include replacing or silencing pathogenic genes and delivering neurotrophic factors. Current preclinical research focuses on developing novel strategies in gene modification to combat neurodegenerative disorders. Numerous clinical trials involving viral vectors in the nervous system are either on-going or completed. Despite these advancements, progress in this field remains constrained by immune responses triggered by viral vectors, which can be triggered through innate and adaptive pathways. The present review will focus on the advances in the development and application of viral vector-based gene therapies for neurodegenerative diseases and summarize the related immune responses, aiming to provide a forward-looking perspective for this emerging arena.